Bovista hollosii—a new puffball (Lycoperdaceae) from sand steppe vegetation in Hungary - Jeppson, Mikael; Finy, Péter; Larsson, Ellen (Phytotaxa, 2016)
A new puffball species, Bovista hollosii, belonging to Bovista subgenus Bovista is described. It is morphologically reminiscent of B. tomentosa but differs in peridial and spore features. Molecular data confirm it as distinct from B. tomentosa. The new species is recorded from sand steppe habitats in Central Hungary. A key to the north and central European species belonging to subgenus Bovista is provided along with illustrations of the new described species.